High-Performance MEA Prepared by Direct Deposition of Platinum on the Gas Diffusion Layer Using an Atomic Layer Deposition Technique. (20th September 2015) - Shu, Ting; Dang, Dai; Xu, Dong-wei; Chen, Rong; Liao, Shi-jun; Hsieh, Chien-te; Su, Ay; Song, Hui-yu; Du, Li
Graphical abstract: Highlights: A highly performance membrane electrode assembly was prepared by ALD technique. The platinum atoms were deposited on the gas diffusion layer directly. The ALD-electrode achieved 2.5 times mass activity of the conventional electrode. Abstract: A high-performance membrane electrode assembly (MEA) with low platinum loading was successfully prepared using an atomic layer deposition (ALD) technique, in which the platinum was directly deposited on the gas diffusion layer to form the catalyst layer. MEAs were fabricated with an ALD-prepared electrode as the anode, and assembled with pretreated Nafion ® membrane (Nafion ® 117) and a commercial cathode. The MEAs were evaluated in a single-cell test station and characterized by cyclic voltammetry (CV), field-emission scanning electron microscope (FE-SEM), high-resolution transmission electron microscope (HRTEM) and grazing incident X-ray diffraction (XRD). The results revealed that the active component, Pt, was highly dispersed in the ALD anode, and the MEA with the ALD anode showed excellent activity and stability. The mass activity reached 4.80 kW g Pt −1, which was 2.53 times higher than that of the MEA with the anode prepared using the commercial catalyst and a conventional screen printing method. In 100 h of durability testing, the ALD–MEA exhibited excellent durability (98.2% voltage retention) compared with the CC–MEA (92.5% voltage retention) when the MEA was discharged at a current density of 400 mA cm −2 . The high performance, along with low platinum loading and high platinum utilization, make the ALD technique promising for use in PEM fuel cells.